Sensorless Direct Torque Control for Interior Permanent-Magnet Synchronous Motors Using Square-Wave-Type Stator Flux Injection at Low-Speed Regions - Cho, Dae Hyun; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2022)
This paper proposes sensorless direct torque control for interior permanent-magnet synchronous motors using square-wave-type stator flux injection at low-speed regions. In direct torque control based on the current model, which is generally used at low-speed regions, a position sensor such an encoder is necessary to obtain the rotor position. However, the usage of the position sensor increases the system cost and volume. To overcome the drawbacks of the position sensor, a sensorless method estimating the rotor position without the use of a sensor is suggested. In the suggested conventional sensorless method, the rotor position is estimated by injecting sinusoidal stator flux, however, signal processing in the conventional method is complex. This paper presents an advanced method of estimating the rotor position using a square-wave-type stator flux injection. In the proposed method, the process for estimating the rotor position is simplified and the time delay decreases due to the elimination of the low-pass filter. The effectiveness of the proposed method is verified via simulation and experimental results.
Keywords: Conventional methods; Current modeling; Direct torque control; Interior permanent magnet synchronous motor; Position sensors; Rotor position; Sensorless direct torque controls; Square waves; Direct torque control; Interior permanent-magnet synchronous motor; Sensorless control; Square-wave-type; Stator flux injection